Impact of Soil and Water Conservation Measures on Soil Physicochemical Characteristics and Crop Productivity: Evidence From Korekore Watershed in the Central Highlands of Ethiopia - Abera Fantahun; Tesfaye Mebrate Lemma; Fikrey Tesfay; Yitea Seneshaw Getahun (The Scientific World Journal)
This study investigates the effects of physical and chemical soil degradation on crop productivity in the Korekore Watershed. The watershed was categorized into level, sloping, and steep slope gradients. Within each slope gradient, one cultivated land managed with soil and water conservation and one cultivated land without soil and water conservation were selected. Selected soil physicochemical analyses were performed on 18 disturbed and undisturbed soil samples and were taken from the top 0–20 cm depths from each cultivated land with three replications. The soil degradation index (SDI) was evaluated based on the percent changes in soil properties of cultivated land without soil and water conservation to that of the cultivated land managed with soil and water conservation. The crop productivity index was determined by analyzing the percentage growth rate and its standard deviation. Soil bulk density and moisture content improved undercultivated land managed with SWC practices. Significantly higher (p≤0.05) soil organic carbon (SOC) content (2.02%), total N (0.12%), available P (4.69 ppm), and exchangeable K (1.33 cmolc/kg) were observed in cultivated land managed with SWC as compared to cultivated land without SWC measures. The value of the SDI (+243.9%) for the watershed has demonstrated that soil degradation has improved and soil and water conservation measures had a significant impact on crop yields. The average crop yield rate (CYR) (30%) was found to be lower than the estimate provided by the central statistics agency in Ethiopia. A higher CYR was observed in cultivated land managed with soil and water conservation practices. It can be concluded that physical and chemical soil degradation significantly impacts crops unless counterbalanced by soil and water conservation measures. Therefore, it is recommended to implement well-integrated watershed management practices to improve soil quality and enhance crop productivity.